Effect of magnification devices on dental students’ visual acuity - Wajngarten, Danielle [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Public Library of Science (PLoS), 2019)
This study aimed to determine dental students’ visual acuity and neck angulation when using magnification devices and distances from the operating field. Forty students from each of the second through fifth years of the five-year program at the School of Dentistry of Araraquara were selected (N = 160). Visual acuity was tested using a miniature Snellen eye chart under five different settings (naked eye; simple loupe; Galilean loupe; Keplerian loupe and an operating microscope). Photographs were taken during the visual acuity exam in order to evaluate the angulation of the subjects’ necks in a neutral posture. The two-factor analysis of variance and the Games-Howell post-hoc test were performed (α = 0.05). A significant difference in visual acuity and neck angulation was found between the magnification device and distance factors in each of the graduating classes analyzed (p<0.05). At a standardized distance, the Keplerian loupe (535.93±133.69), the Galilean loupe (514.06 ±171.56), and the operating microscope (517.71±161.61) all provided greater visual acuity. At a subjectively comfortable distance, the Keplerian (521.35±157.99) and Galilean (515.00 ±156.32) loupes produced the best visual acuity. The angulation of the neck was greater when the simple loupes (56,59±10,88) and naked eye (56.51±13.55) were used at a subjectively comfortable distance. At both a standardized distance and a comfortable distance, the Galilean and Keplerian magnification systems provided the best visual acuity and the lowest angulation of the operator’s neck. At a standardized distance of 30 cm to 40 cm, the operating microscopes produced similar results.